"Examined Masculinity": Bi + Men's Experiences of Sexuality and Gender across Heteronormative & Queer Spaces. Issue 1 (2nd January 2023) - Anders, Christopher; Stuart-Maver, Shannon L.; Hong, Jung Eui; Amos, Echo
Abstract: Bi + individuals make up the largest proportion of the LGBTQ + community (Gates, 2011 ), but are often underrepresented in the literature (Galupo at al., 2017). Most research on bi + experiences focuses on discrimination (Roberts et al., 2015 ; Sarno et al., 2020 ; Weiss, 2003 ), whereas less research has examined the ways in which bi + men develop their own self-concepts of gender and sexuality while facing negative stigmatization and erasure from both heterosexual and queer communities. This study implements Consensual Qualitative Research (CQR; Hill et al., 1997 ; Hill et al., 2005 ) to examine the question: how do bi + men develop and express their masculinity and sexuality while moving between and within heteronormative and queer sociocultural spaces? Findings consist of six domains including: (1) Beyond labels; (2) Fighting for authenticity; (3) Policing identity; (4) Importance of social support; (5) Intersecting identities; and (6) Family influence. Ultimately, bi + men described flexibility in their gender and sexual identities, a resilient pursuit of authenticity amidst negative experiences and ostracization from possible spaces in which to explore identity, the influence of racial, religious and cultural values on their identity development, and the invaluable nature of an affirming, accepting and encouraging environment.